EFL Teachers’ Continuous Professional Development in the Use of E-Learning Materials in Indonesia: Perception, Needs and Challenges - Mandasari, Ghassani; Dewi, Ratna Sari; Jaya, Ervan (Journal of English Language Teaching, Linguistics, and Literature Studies, 2024)
This study aimed at describing the teachers’ perceptions, needs and challenges to the EFL Secondary teachers in using E-Learning Materials which contributed to the improvement of EFL teachers’ E-Learning personal and professional competency development. This research applies qualitative methods and uses case study as the research design. This research comprises a sample of 140 EFL teachers in Indonesia. The data was collected through questionnaire, interview to the participants and documentation of English learning materials and media. Then, the data was analysed by applying three techniques; data reduction, data display, and data verification. The results revealed that the perceptions of the teachers are they have adequate overview and competency for CPD E-Learning materials. Meanwhile, the needs of the teachers in the CPD E-learning activities should cover the combination of learner-led and e-coaching mode in the CPD E-Learning and served with both local and native experts to synchronise the local and authentic context. However, the researchers found that the challenges faced by the teachers are connectivity, teaching load and students’ varied competency.Keywords:     CPD E-learning materials, EFL, online learning